A new marsupialiform from Upper Cretaceous of Songliao Basin, Heilongjiang, China - Gao, Yuan; Wu, Wen-Hao; Mao, Fang-Yuan (Palaeoworld, 2025)
The fossil record of marsupialiforms in the Upper Cretaceous of Asia is scarce, without previous discoveries in China until the current study. Here we report a new marsupialiform, Solatherium nenjiangensis n. gen. n. sp., based on three lower left molars found in the early Campanian Nenjiang Formation at the Bei’an locality of Songliao Basin. The lower molars of S. nenjiangensis exhibit a well-developed entoconid, which is significantly larger than the hypoconulid and the twined entoconid-hypoconulid that is lingually positioned; the entoconid is taller than the hypoconid. These characteristics are consistent with the lower molars of “pediomyids”, placing S. nenjiangensis within the Family “Pediomyidae”. Furthermore, a marsupialiform lower molar is identified as an undetermined species due to its distinct features from those of S. nenjiangensis, indicating a different taxon. This discovery marks the first occurrence of marsupialiform teeth in China and potentially represents the initial recognition of “pediomyids” in Asia, enhancing our understanding of the geographic distribution of marsupialiforms and offering valuable insights into the evolution and migration of metatherians.